CONTEMPORARY GEODYNAMICS OF THE GAROMAI ACTIVE FAULT (SAKHALIN ISLAND) - N. F. Vasilenko; A. S. Prytkov (Геодинамика и тектонофизика, 2019)
In the northern Sakhalin Island, the tectonic activity of the fault zones is a potential threat to the industrial infrastructure of the petroleum fields. Recently, the background seismicity has increased at the Hokkaido‐Sakhalin fault that consists of several segments, including the Garomai active fault. In the studies of the regional deformation processes, it is important not only to analyze the seismic activity, but also to quantitatively assess the dynamics of deformation accumulation in the fault zones. In order to study the contemporary geodynamics of the Garomai fault, a local GPS/GLONASS network has been established in the area wherein trunk oil and gas pipelines are installed across the fault zone. Based on the annual periodic measurements taken in 2006–2016, we study the features of surface deformation and calculate the rates of displacements caused by the tectonic activity in the fault zone. During the survey period, no significant displacement of the fault wings was revealed. In the immediate vicinity of the fault zone, multidirectional horizontal displacements occur at a rate up to 1.6 mm/yr, and uplifting of the ground surface takes place at a rate of 3.4 mm/yr. This pattern of displacements is a reflection of local deformation processes in the fault zone. At the western wing of the fault, a maximum deformation rate amounts to 1110–6 per year. The fault is a boundary mark of a transition from lower deformation rates at the eastern wing to higher ones at the west wing. In contrast to the general regional compression setting that is typical of the northern Sakhalin Island, extension is currently dominant in the Garomai fault zone. The estimated rates of relative deformation in the vicinity of the Garomai fault give grounds to classify it as ‘hazardous’.